2021
DOI: 10.1017/s0022215121000414
|View full text |Cite
|
Sign up to set email alerts
|

Unusual complications of bone wax at the skull base

Abstract: Objective This study aimed to describe the clinical presentation, microbiological profile and management of complications of bone wax usage for surgical procedures at the skull base. Method The case records of a series of five patients who developed post-operative surgical site complications because of bone wax usage during skull base surgery were reviewed. Results In all five patients, persistent site-specific clinical features were noted along with intra-operative pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A. fumigatus is ubiquitous in the environment and commonly transmitted through conidial inhalation. Pasqualloto et al reported 25 cases of aspergillosis due to neurosurgery, and Panicker et al described 5 others due to combined ear, nose, and throat and neurosurgical procedures [ 5 , 13 ]. In addition to the inhalational route, the central nervous system (CNS) may also be a destination from hematogenous dissemination or directly spread from nasal or paranasal deposits.…”
Section: Discussionmentioning
confidence: 99%
“…A. fumigatus is ubiquitous in the environment and commonly transmitted through conidial inhalation. Pasqualloto et al reported 25 cases of aspergillosis due to neurosurgery, and Panicker et al described 5 others due to combined ear, nose, and throat and neurosurgical procedures [ 5 , 13 ]. In addition to the inhalational route, the central nervous system (CNS) may also be a destination from hematogenous dissemination or directly spread from nasal or paranasal deposits.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 This aligns with the observation that Staphylococcus Aureus is a predominant pathogen in bone wax-related infections. 10,12 Different fungal infections have also been reported. 12 It is hypothesized that the malleable bone wax is manipulated by the surgeon later in surgery, when the probability of contamination is higher.…”
mentioning
confidence: 99%
“…10,12 Different fungal infections have also been reported. 12 It is hypothesized that the malleable bone wax is manipulated by the surgeon later in surgery, when the probability of contamination is higher. 10 In addition, the effect of bone wax on inhibiting bone healing and osteogenesis has been consistently demonstrated in various animal and human studies.…”
mentioning
confidence: 99%